Interview with Volunteers for Saving Ukrainian Cultural Heritage Online (SUCHO). Issue 3 (12th July 2022) - Jones, Edgar; Kijas, Anna E.; Wingate, Alex; Bowen, Jennifer; Diken, Taylor; Martin, Kim; Rakityanskaya, Anna; Kisselstein, Katherine G.; Spectre, Rob
Abstract: An interview with eight volunteers involved in creating metadata for online resources identified for inclusion in the Saving Ukrainian Cultural Heritage Online (SUCHO) project. Includes background and an introduction to the project, a discussion of SUCHO as a volunteer-driven project, a description of the metadata aspect, and an online demo of the process of creating metadata for the project.